The Role of NLRP3 Inflammasome in IgA Nephropathy - Xiaofang Wu; Lei Zhao; Kailong Li; Jurong Yang (Medicina, 2022)
Immunoglobulin A nephropathy (IgAN) is the most common primary glomerular disease worldwide today. The NLRP3 inflammasome is a polyprotein complex and an important participant in inflammation. Accumulating studies have shown that the NLRP3 inflammasome participates in a variety of kidney diseases, including IgAN. This review focuses on the role of the NLRP3 inflammasome in IgAN and summarizes multiple involved pathways, which may provide novel treatments for IgAN treatment.